Optimal ranking and directional signature classification using the integral strategy of multi-objective optimization-based association rule mining of multi-omics data - Mallik, Saurav; Seth, Soumita; Si, Amalendu; Bhadra , Tapas; Zhao, Zhongming (Frontiers in Bioinformatics, 2023)
We are grateful to the reviewer for his valuable suggestions. In minor revision, we have made our best effort on enhancing the manuscript within the short time set by the organizers. We have substantially made the needed improvement and also discussed the asked features and limitations. Following is our point-to-point response to the reviewers' comments.Reviewer #3:Comment 1: The author addressed the majority of my concerns. One minor thing is to correct the legend for the Figure 5: the light black line and blue curve; and explain the points shown in the figures, such as 0.536.Response: Thank you so much Reviewer #3 for the appreciation on our revised manuscript. As suggested, we corrected the legend of caption for Figure 5 and included the explanation briefly on the aforementioned point. See page 30.